Draft Annual Plan 2000-2001 Volume I (Part II) Government of Uttar Pradesh - Planning Commission (Planning Commission, 2000)
Improving agricultural production by better watershed management with an integrated approach of soil and water conservation. Strengthening of transfer of technology and agricultural extension net work through strong extension support from Govt, functionaries with due support of farmers user group, self-help group and the NGOs. Better land resource utilization i.e. improved use of problem soils like user, ravine etc., by way of scientific reclamation and reduction of culturable waste and the fallow. Intensification of cereal-based cropping systems to ensure food security under appropriate agro-climatic situations to harness comparative advantages of given agro-climatic zone. Increasing efficiency of inputs use through Integrated Plant Nutrient Management (IPNM), On-farm Water Management, Conjunctive water use and use of Bio-Fertilizers, Green manuring , FYM , Compost, Micro Nutrients etc.
Draft Annual Plan 2000-2001 Volume I (Part II)
Government of Uttar Pradesh